Endoscopic ultrasonography: an advancing option with duality in both diagnosis and treatment of gastrointestinal oncology - Chen, Fenglin (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Since their introduction into the clinical practices in 1980s, techniques of endoscopic ultrasonography (EUS) have been rapidly developing and are now in widespread use in gastrointestinal oncology. Evolving from the classical option, EUS today has been much innovated with addition of a variety of novel ideation which makes it a powerful tool with encouraging duality for both diagnostic and therapeutic purposes. There is a dire need for physicians in this field to understand the status quo of EUS as related to the management and detection of gastrointestinal tumors, which is globally reviewed in this paper.